2001
DOI: 10.1083/jcb.153.5.1023
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Met Receptor by Cell Attachment Induces and Sustains Hepatocellular Carcinomas in Transgenic Mice

Abstract: Overexpression is the most common abnormality of receptor tyrosine kinases (RTKs) in human tumors. It is presumed that overexpression leads to constitutive activation of RTKs, but the mechanism of that activation has been uncertain. Here we show that overexpression of the Met RTK allows activation of the receptor by cell attachment and that this form of activation can be tumorigenic. Transgenic mice that overexpressed Met in hepatocytes developed hepatocellular carcinoma (HCC), one of the human tumors in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
221
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 259 publications
(231 citation statements)
references
References 49 publications
7
221
3
Order By: Relevance
“…However, expression of CD82 failed to inhibit this signaling pathway, suggesting the possibility that this may be a non-CD82-regulated invasion pathway. Our data support recent evidence for the existence of crosstalk between integrins and c-Met (Wang et al, 1996(Wang et al, , 2001Trusolino et al, 2001). Our data further suggest that CD82 may be regulating this crosstalk.…”
Section: Cd82 Regulates C-met Signaling Sc Sridhar and Ck Mirantisupporting
confidence: 92%
See 2 more Smart Citations
“…However, expression of CD82 failed to inhibit this signaling pathway, suggesting the possibility that this may be a non-CD82-regulated invasion pathway. Our data support recent evidence for the existence of crosstalk between integrins and c-Met (Wang et al, 1996(Wang et al, , 2001Trusolino et al, 2001). Our data further suggest that CD82 may be regulating this crosstalk.…”
Section: Cd82 Regulates C-met Signaling Sc Sridhar and Ck Mirantisupporting
confidence: 92%
“…Thus our data indicate that in highly invasive cells that adhere, migrate, and invade well on laminin, CD82 expression does not change integrin expression, but rather acts downstream of integrin engagement. c-Met, the receptor for HGF/SF, is known to regulate migration and invasion and has been implicated in promoting metastasis in many different kinds of cancers (Pisters et al, 1995;Birchmeier et al, 1997Birchmeier et al, , 2003Wang et al, 2001), including prostate cancer (Humphrey et al, 1995;Nishimura et al, 1998;Knudsen et al, 2002;van Leenders et al, 2002;Nakashiro et al, 2003;Knudsen and Edlund, 2004). Previous studies in a mammary tumor cell line demonstrated that CD82 expression attenuated EGF-mediated EGFR signaling and reduced migration (Odintsova et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…c-MET was initially identified as an oncogene expressed by a transformed human osteogenic sarcoma cell line (Cooper et al, 1984). Since then, strong evidence of a role for MET signaling in human cancer has come from work in cell culture models (Maulik et al, 2002), mice (Takayama et al, 1997;Wang et al, 2001), and humans with sporadic and hereditary forms of renal carcinoma, where germline and somatic missense mutations were identified in MET's kinase domain (Schmidt et al, 1997(Schmidt et al, , 1998. In addition to tumorigenesis, MET activity plays a significant role in promoting tumor cell invasion and metastasis (Rong et al, 1994;Ma et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The trans-activation of growth factor receptors by integrins is an emerging field. Recently, an interesting study showed that cell adhesion, presumably through integrins, activates the human HGF receptor, c-Met, while overexpression of c-Met in hepatocytes resulted in hepatocellular carcinoma in mice (Wang et al, 2001). Most significantly, this effect of c-Met is independent of binding of HGF, suggesting that integrin-dependent trans-activation could be responsible for tumourigenesis.…”
Section: Migration and Proliferation Of Endothelial Cellsmentioning
confidence: 99%